Moroccan female leaders between femininity and masculinity: A case study of Nabila Mounib (the first female leader of a political party) - El Fattah, Fatima Ezzahraa (International Journal of Linguistics and Translation Studies, 2022)
Women are ‘intruders’ in the political world, they often find themselves at odds with a world that has established its values and rules according to men’s ways of doing things. When women enter politics, their socially constructed gender clashes with the tough world of politics. Often the feminine style collides with doing political leadership, a leadership that requires toughness, assertiveness and even violence. Women are socially constructed to behave in the complete opposite of this values. The first Moroccan female leader was elected as the head of her political party, Partie Socialist Unifié [PSU], in 2012. Nabila Mounib was faced with the dilemma of how she is going to lead a political party as a female in a patriarchal and conservative society. Should she lead using her feminine leadership style or should she adapt the masculine style that seems to conform with the political world? This paper attempts to explore her leadership style using Feminist Critical discourse analysis FCDA with a focus on the following linguistic features: interruption, hedges and tag questions, and the I vs We.